Pengalaman Komunikasi Santriwati Dalam Menonton Drama Korea - Ramadhani, Muthiara; Utamidewi, Wahyu; Lubis, Flori Mardiani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to understand the communication experiences of female Islamic boarding school students (santriwati) in watching Korean dramas. The research method used is a qualitative method phenomenology approach. The research data was obtained through in-depth interviews and participant observation with santriwati who have experience in watching Korean dramas. The results of the study show that the communication experiences of santriwati in watching Korean dramas involve aspects such as emotional involvement, identification with characters, exploration of Korean culture, and the use of social media. In this context, santriwati express that watching Korean dramas provides them with strong emotional experiences, such as feeling connected to the characters, experiencing the same emotions, and sharing happiness or sadness together. They also develop identification with the characters in Korean dramas, associating their own struggles and feelings with the stories depicted. Moreover, watching Korean dramas provides an opportunity for santriwati to learn about Korean culture. They are interested in traditional clothing, food, music, and social customs portrayed in the dramas. Some of them are even interested in learning the Korean language. Korean dramas also provide insights into everyday life in Korea and broaden their knowledge of the world. The use of social media is also an important part of santriwati's communication experiences in watching Korean dramas. They use social media platforms such as Facebook, Twitter, and Instagram to share opinions, emotions, and recommendations about the dramas they watch. Social media also serves as a platform for them to connect with other Korean drama fans, both within and outside the santriwati community. This research provides a deep understanding of the communication experiences of santriwati in watching Korean dramas. The findings of this study can provide insights to cultural enthusiasts, drama producers, and other researchers on how Korean dramas can influence the emotions, identity, and social interactions of santriwati. The implications of this research can also be used in the development of cultural content and intercultural understanding among santriwati. Keywords: Communication experiences, santriwati, Korean dramas.